Outcome of Urethral Stricture Managed by Different Surgical Techniques - Muhammad Mohsin Ayaz, Zeeshan Ahmad, Muhammad Asif, Shahid Ali, Abdullah, Tufail Hussain Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcome of urethral stricture managed by different surgical techniques. Place and Duration: This Study was conducted at Lahore General Hospital, Lahore in the duration from May, 2022 to October, 2022. Methods: This randomized controlled trial was conducted on 60 patients divided equally in two groups. Both groups were assessed for maximum urinary flow 6 months after surgery, cause of the stricture, site of the stricture and success rate was assessed between both variables. T-test and Chi Square test with P < 0.05 as statistically significant were used to assess various outcomes between both groups. Results: The mean age in urethroplasty group was 44.43±10.618 years while in endoscopic urethrotomy group the mean age was 48.23±11.790. Urethroplasty was significantly successful in 80% patients whereas endoscopic urethrotomy was successful in 43.3% patients (P = 0.003). Conclusion: Urethroplasty is a safe and effective technique for treatment of urethral stricture. Keywords: Urethral stricture, Urethroplasty, Endoscopic urethrotomy, Efficacy